ACTIVITIES OF THE CHILDREN’S FRIENDS ’SOCIETY FOR CHILDREN AND THEIR FAMILIES AT RISK OF SOCIAL EXCLUSION - Beiger, Galina; Borysiuk, Svitlana (Mountain School of Ukrainian Carpaty, 2021)
The article is an analysis of the achievements of the Society of Friends of Children - the oldest non-governmental organization in Poland operating for the benefit of the child and his family. The focus of this organization is on children at risk of social exclusion due to poverty, neglect, orphanage or disability and their families. From the beginning of its operation, in from 1919, the Society responded vividly to the care and educational needs of children and established various day and 24-hour facilities providing them with decent conditions for development, and support for families. After the end of World War II, it took special care of orphaned children returning from exile and concentration camps, hungry, homeless and neglected in education. In later years, TPD organized orphanages, kindergarten camps, environmental educational centers, and youth clubs. It established 6 adoption centers which qualified orphaned children to adoptive families. It conducted an extensive campaign of organizing summer and winter recreation for children from dysfunctional families and specialized summer camps for sick and disabled children. n the 1990s, the Society established a number of innovative, specialized institutions, such as community clubs - including sociotherapeutic centers, centers for children and families, rehabilitation centers, family counseling centers, crisis intervention centers as well as recreation centers and children's holiday homes. The work of the Society for the benefit of the child and the family is based on the principles of competence, creativity and comprehensiveness. In his current activities, he prefers the principles of: equal opportunities for all children to be brought up in the family, the subjectivity and dignity of the child, protection of his rights and education in the spirit of tolerance, respect and mutual assistance. To this end, in many cities, about one hundred social ombudsmen for children's rights have been appointed, who intervene in situations of child abuse, and solve conflict and care-and-education situations in families. In many areas of care, the Society was a pioneer, and the forms of care initiated by it entered the national childcare system in Poland.